THE BALLET "TOMARIS" IN THE CULTURE OF UZBEK BALLET PLACE AND SIGNIFICANCE - Farangiz Ikromova (Journals Park Publishing, 2022)
This article provides information about the history of the Uzbek ballet, its stages of development. The role and function of the choir in the ballet "Tomaris" written by the famous composer, Honored Artist of Uzbekistan Ulugbek Musayev will also be considered in detail.
Keywords: ballet; choreography; drama